PS 05-58 ARTERIAL HYPERTENSION AND PULSE PRESSURE: RELATIONSHIP WITH PULSE WAVE VELOCITY. (September 2016) - Ramirez, Agustin; Tringler, Matias; Galli, Cintia; Diaz, Alejandro; Fischer, Edmundo Cabrera
Abstract : Objective: Pulse Pressure (PP) and pulse wave velocity (PWV) are related to cardiovascular risk (CVR). We evaluated in patients with arterial hypertension (HT), as unique risk factor, the impact of arterial hypertension on PP and PWV, the mean and age related PWV values, the relationship between PP and PWV and the rate of changes with aging. Design and Method: 1079 subjects were randomly enrolled and 299 selected as selected as asymptomatic non-smoking hypertensive patients (HT; 50 ± 14.8years old), as the only risk factor. Blood pressure was measured in the sitting position, after 10 min rest, 3 times (Omron model 705IT), elapsed by 1 min. After that, PP was calculated as: SBP-DBP. The mean value was considered as the PP value for each subject. Carotid-femoral PWV was measurements were performed continuously for at least 10 cardiac cycles and the mean value considered as PWV value for each patient. Results: In HT, mean PWV value was 8.04 ± 1.8 m/s and increased linearly with age (r = 0.49; p < 0.001) being the year growing of 0.062 ± 0.006 m/sec (p < 0.001) without. In HT, PP increases linearly with aging (r = 0.155; p < 0.01) with a progressive year related increase (0.138 ± 0.051 mmHg/year; P < 0.001). No gender differences were found (56.31 ± 12.89 mmHg versus 54.58 ± 13.62 mmHg; p = 0.338). Finally, PWV and PP in HT showed a significant positive correlation (r = 0.191, p < 0.001). Conclusions: All these data suggest that, in HT patients, PP, as PWV, could be a reliable marker of arterial dysfunction. This is supported by the fact that PP and Arterial stiffness, evaluated as PWV are age dependent without differences in gender and were significantly related.